Analysis of Minimalist Consumption Behavior and Financial Goal Orientation as Predictors of Long-Term Savings Discipline and Budgeting in Generation Z in Jakarta - Herlin, Faradilla; Sukma Nirwana, Nihlatul Qudus; Supriandi, Supriandi (West Science Interdisciplinary Studies, 2025)
This study explores the influence of minimalist consumption behavior and financial goal orientation on budgeting practices and long-term savings discipline among Generation Z in Jakarta. Using a quantitative approach, data were collected from 150 respondents via a Likert-scale questionnaire and analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS). The findings reveal that financial goal orientation and minimalist consumption behavior significantly impact both budgeting and savings discipline. High R2 and Q² values confirm the model’s explanatory and predictive relevance. The results underscore the importance of promoting financial goal-setting and minimalist behaviors to enhance financial management practices in Generation Z. Practical and theoretical implications are discussed, with recommendations for policymakers and educators to design targeted financial education programs.
Keywords: Minimalist Consumption Behavior; Financial Goal Orientation; Budgeting Practices; Long-Term Savings Discipline; Generation Z